(untitled) (Castilla. Estudios de Literatura, 2010)
The classic detective literary convention had been transformed several times before the detective-fiction genre was created by the end of the 19th century. It presented the adventures of individuals that entwined criminal mysteries. It is undeniable that its prestige in the literary world has risen, especially since the middle of the 20th century, when there appeared such literary genres as the metaphysical detective story that endowed plot elements with a philosophical meaning. In Spanish America, since the turbulent times of various political and social problems of the second half of the 20th century, writers have developed many ways of depicting the social and political crime scene thanks to modifying diverse literary conventions of the detective story. A good example is the creation of the Bolivian author Edmundo Paz Soldán (1967) who merged the metaphysical detective story with critical perspective: it describes contemporary Bolivians, citizens of the global village who are still preoccupied with the “premodern” social and political issues in their country.